Argumentation and Persistent Disagreement - Castro, Diego (Informal Logic)

(untitled) (Informal Logic, 2021)
Some disagreements seem to be persistent: they are, pretty much, immune to persuasive argumentation. If that is the case, how can they be overcome? Can argumentation help us? I propose that to overcome persistent disagreements through argumentation, we need a dynamic and pluralistic version of argumentation. Therefore, I propose that argumentation, more than a tool that uses persuasion to change the mind of the counterpart, is a toolbox that contains persuasion, deliberation, negotiation, and other dialogical strategies that can be used to reach an agreement.